Formación profesional contextualizada en Economía para Directivos Empresariales - Cruz Montero, Juan José (2021)
In the economic conditions pos COVID-19, is more necessary to contribute to the reflection on the role of managers in economic-financial management to achieve business efficiency, as well as on the role that manager training plays in these matters. In this article it is aspired to like objective: submitting a proposal, scientifically well-founded, for the curricular framing of the training in economy of the of managers, tempered to the conditions of the Economic and Social model and applied in the Cuban sugar sector. On the whole the methods were used system focusing, the historic-logic, the opinion polls and the interview with directives and teachers, implicated directly in the economical preparation, and the need that the economical training to directives should be readjusted to the new normality and to its impact; was ratified. As results, a synthesis of the results of the diagnosis is presented that demonstrates the need for the proposal, the conceptualization of three essential operational terms and the proposal of curricular structuring for the training in economics of managers that is characterized by being flexible, contextualized and systemic. Its theoretical validation was carried out through the criteria of experts and in practice it is validated by prospecting scenarios, both of which demonstrate their feasibility. The most important final conclusion is that a curricular structuring of managerial training; systemic, flexible, contextualized, structured by levels and using training routes, it meets the conditions to satisfy the requirements of the national Economic and Social Model.